2004
DOI: 10.1097/00001503-200410000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia and perioperative outcome: what is new?

Abstract: Despite the controversies, the numerous potential benefits and advantages of regional anesthesia are keys to its continued popularity. With constant search for new scientific clues by improving experimental designs, valuable evidence slowly unfolds. Regional anesthesia certainly takes a leading role in the current trends for a multimodal approach of perioperative pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…TEA has been associated with earlier mobilization, reduced opioid consumption, and improved cough, and thus, it has beneficial effects on lung functions causing diminished incidences of atelectasis or pneumonia [15,24]. In another meta-analysis including only CABG, patients reported faster extubation and less pulmonary complications with thoracic epidural blockade [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEA has been associated with earlier mobilization, reduced opioid consumption, and improved cough, and thus, it has beneficial effects on lung functions causing diminished incidences of atelectasis or pneumonia [15,24]. In another meta-analysis including only CABG, patients reported faster extubation and less pulmonary complications with thoracic epidural blockade [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed that TEA causes reduced incidence of atelectasis in comparison to LEA. No permanent neurological sequelae were reported in a total of 4,185 patients with use of TEA; however, temporary neurological sequelae such as peripheral nerve injury or dural tap-related headache are much more frequent [24]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the debate whether epidural analgesia improves outcome has not been settled. 11 For colorectal surgery, epidural analgesia decreased postoperative pain and ileus rate, with no effects on hospital stay. 12 In patients undergoing abdominal aortic operations, epidural anesthesia and analgesia improved overall outcome and decreased intubation time and ICU stay.…”
Section: Introductionmentioning
confidence: 99%
“…Epidural analgesia has become a popular analgesic technique for abdominal surgery with high efficacy and safety. However, the debate whether epidural analgesia improves outcome has not been settled . For colorectal surgery, epidural analgesia decreased postoperative pain and ileus rate, with no effects on hospital stay .…”
Section: Introductionmentioning
confidence: 99%
“…Several published manuscripts in recent years on the potential non-analgesic applications of regional anesthesia encourage us to expand its role from intraoperative to the perioperative period. However, its clinical advantages are not fully disclosed and even its overall beneficial effect on patient outcome is still controversial (1).…”
mentioning
confidence: 99%